Evaluation of a user‐friendly CSDS cage apparatus for studying depressive‐like behaviors in rodents - Hao Zhang; Dongmei Gao; Minghu Hu; Wanqing Zhou; Muxuan Han; Ya Sun; Yang Zhang; Jieqiong Wang; Mingzhou Gao (Animal Models and Experimental Medicine)
Abstract Background Previously, a chronic social defeat stress (CSDS) model has been widely‐adopted for assessing depressive‐like behaviors in animals. However, there is still room for improvement in the CSDS model to safeguard study accuracy and the welfare of lab rodents. Our study team developed a novel, standardized apparatus to induce CSDS in rodents and assessed the model's practical adaptability. Methods An innovative CSDS cage apparatus and water bottle was designed. To evaluate the effectiveness of the newly developed tools, a variety of animal models, including the tail suspension test (TST), sucrose preference test, forced swimming test (FST), novelty‐suppressed feeding test, female urine sniffing test, and open field test (OFT), were adopted to assess depressive‐like behaviors in mice. Fluoxetine treatment was also administered to observe the reversal effect, as part of the validation. Results The CSDS cage apparatus resulted in the manifestation of depressive‐like behaviors in the model mice. Significant reductions in sucrose preference and urine sniffing time were observed, while the OFT revealed decreased central zone total distance, residence time, and frequency of entry. Moreover, increased immobility was found in the FST and TST. Fluoxetine treatment was found to successfully reverse the modeling effect. Conclusion The CSDS cage apparatus was validated for enhanced usability and addressed the previous challenges of water bottle leakage and lab rodent welfare issues. The consistent results from multiple behavioral tests also supported real‐world application of the apparatus, offering researchers a promising alternative to conventional rodent cages.